(untitled) (Eurasian Medical Research Periodical, 2022)
Healthy soil is essential for human health. Depending on the condition and composition of the given soil, this effect can be positive or negative, direct or indirect. Soils in the Southern Borderlands have a major impact on human health and well-being. Soils that affect human health typically include natural soils and agroecosystems with low anthropogenic pollution, soils in cities, mines, oil and gas production sites, landfills, and other places where anthropogenic pollution is likely to be high. Soil can be contaminated with toxic chemical elements and substances either naturally or as a result of anthropogenic influence. A change in the amount of any element can cause a person to be poisoned by the elements necessary for life. For any essential element, there is an optimal concentration range in humans, below this optimal range leads to deficiency, while concentrations above the optimal range cause toxicity, ore pathological condition.